2004
DOI: 10.1063/1.1753070
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of the thermoelectric layered cobalt oxides measured by the Harman method

Abstract: In-plane thermal conductivity of the thermoelectric layered cobalt oxides has been measured using the Harman method, in which thermal conductivity is obtained from temperature gradient induced by applied current. We have found that the charge reservoir block (the block other than the CoO2 block) dominates the thermal conduction, where a nano-block integration concept is effective for material design. We have further found that the thermal conductivity shows a small but finite in-plane anisotropy between a and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 21 publications
3
47
0
3
Order By: Relevance
“…In Ref. 54 56,57 These experiments report the intrinsic thermal conductivities of these crystals, for instance for NaCoO 2 , to vary from 5-15 W/mK with varying intercalation of Na.…”
Section: Battery Electrode Microstructures-mentioning
confidence: 99%
“…In Ref. 54 56,57 These experiments report the intrinsic thermal conductivities of these crystals, for instance for NaCoO 2 , to vary from 5-15 W/mK with varying intercalation of Na.…”
Section: Battery Electrode Microstructures-mentioning
confidence: 99%
“…The FK model that describes the effects of a typical on-site potential has been studied extensively [2]. As we mentioned in the Introduction to paper Ⅰ, one of our motivations for studying this system was that very low lattice-thermalconductivity was found experimentally for some materials consisting of two interpenetrating incommensurate sub-lattices, such as Na x CoO 2 [3], Ca 3 Co 4 O 9 [4,5], and Bi 2−x Pb x Sr 2 Co 2 O y [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this is that these materials have very low lattice thermal conductivity [3]. To understand their lattice thermal conductivity, we need to know the lattice vibrational properties of two inter-penetrating sublattices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations revealed that materials consisting of two interpenetrating incommensurate sub-lattices, such as Na x CoO 2 [1], Ca 3 Co 4 O 9 [2,3], and Bi 2−x Pb x Sr 2 Co 2 O y [2,4], have very good thermoelectric properties. One reason for this is that these materials have very low lattice thermal conductivity [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation